EU terrorism situation and trend report TE-SAT / EUROPOL / 2017 (EU terrorism situation and trend report TE-SAT, 2017)
This new edition of the yearly EU Terrorism Situation and Trend Report (TE-SAT), which Europol has produced since 2007, provides a concise overview of the nature of terrorism that the EU faced in 2016. In this report you will find information on terrorist attacks that occurred in 2016 and the numbers of arrests and convictions for terrorist offences. Also included is a brief overview of the terrorist situation outside the EU.